Penerapan Pasal 34 Ayat (1) Kitab Undang-Undang Hukum Acara Pidana Dalam Hubungannya Penggeledahan Tanpa Izin - Fandiwinata; Dahnial Jaka Aditia; Ryan Martha Wijaya; Deontino Syaputra; Iin Syaifia Putri (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
A search is an action by investigators that is permitted by law to enter and examine a person's body and clothing or the home where they reside. In addition to conducting inspections, they can also carry out arrests and seizures at the same time. The research method used in this paper is normative or doctrinal legal research. The data source used in this research is legal materials that have been studied and analyzed. With the permission of the Chief of the District Court, the search can be conducted immediately.